De vulgarisatie van de totale kastratie van de Ram in het verre noorden van Kameroen: Een voorbeeld van een niet-verantwoorde promotie van een technologie - Thys, Eric (Afrika Focus, 1991)
The problem of a not justified promotion of a technique is explained through the example of the total castration in sheep in a sahelo-soudanian area of Africa. The actual situation of the total castration in sheep and the influence on some zootechnical parameters are studied in the far north of Cameroon. No benefit of this promotion has been observed in the local socio-economical environment. More emphasis has to be laid on the improvement of feeding and on a better flock management. In regard to the better understanding of problems in livestock extension, a multidisciplinary approach is recommended. KEY WORDS: castration, meat production, multidisciplinarity, sahelo-soudanian Africa, sheep, transfer of technology, zootechny